Способы формирования и оснастка при производстве уникальных твердосплавных изделий на ГНПП «Алкон-твердосплав» - Василенко, Л.Е.; Барановский, А.М.; Сотникова, Л.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The paper presents procedures of producing unique hard alloy articles, gives designs of press molds and tooling which make it possible to improve the article quality, reduce machining allowances and to lower labour intensity of pressing and drawing articles out of press molds.